HUBUNGAN MODAL SOSIAL DAN UNSUR TUMBUH KEMBANG PARTISIPASI MASYARAKAT DALAM PROGRAM KELUARGA HARAPAN - Nurul Risca Pratiwi; Agung Wibowo; Bekti Wahyu Utami (AGRITEXTS: Journal of Agricultural Extension, 2016)
This research aims to assess the level of social capital, assess the level of an element of growth and development participation, and examines the relationship between capital social and an element of the growth of participation on CCT in Wonogiri Subdistrict of Wonogiri Regency. Location research done purposively and taking the number of samples is done by proportional random sampling. Methods of data analysis is the measurement interval width and Rank Kendall correlation test. Based on the results of correlation Rank Kendall, a variable that has a significant relationship with the participation of KSM in CCT at all stages of participation is variable reciprocity the value Zcount 3.808, solidarity with Zcount 5.771, willingness with Zcount 4.326, opportunity with Zcount value of 5.716, and the ability with a value of 4,435 Zcount. It shows that the variable relationship reciprocity, solidarity, willingness, opportunity, and ability with the participation of KSM in PKH is significant because the value of Ztable is greater than Zcount 2,580 at 99% confidence level. Thus,  the  higher  the  level  of  reciprocity,  solidarity,  willingness,  opportunity,  and ability to KSM, the higher the participation in CCT.